2019
DOI: 10.1111/ppl.12872
|View full text |Cite
|
Sign up to set email alerts
|

The urea transporter DUR3 contributes to rice production under nitrogen‐deficient and field conditions

Abstract: Nitrogen is one of the most important elements for plant growth, and urea is one of the most frequently used nitrogen fertilizers worldwide. Besides the exogenously-supplied urea to the soil, urea is endogenously synthesized during secondary nitrogen metabolism. Here, we investigated the contribution of a urea transporter, DUR3, to rice production using a reverse genetic approach combined with localization studies. Tos17 insertion lines for DUR3 showed a 50% yield reduction in hydroponic culture, and a 26.2% y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Another gene, OsDUR3 (LOC_Os10g42960), a high-affinity urea transporter, was upregulated under low N, confirming earlier studies [21,46]. Since OsDUR3 improved the rice yield under nitrogen deficient conditions by increasing urea uptake [47], the increased expressions of OsDUR3 should help in N foraging. Therefore, the upregulation of both OsDUR3 and OsNRT2.1 may be enhancing N foraging in the form of either nitrate or urea.…”
Section: Discussionsupporting
confidence: 81%
“…Another gene, OsDUR3 (LOC_Os10g42960), a high-affinity urea transporter, was upregulated under low N, confirming earlier studies [21,46]. Since OsDUR3 improved the rice yield under nitrogen deficient conditions by increasing urea uptake [47], the increased expressions of OsDUR3 should help in N foraging. Therefore, the upregulation of both OsDUR3 and OsNRT2.1 may be enhancing N foraging in the form of either nitrate or urea.…”
Section: Discussionsupporting
confidence: 81%
“…As the core structural element of proteins, including enzymes and those involved in photosynthetic systems, nitrogen (N) is a key factor in crop growth and productivity (Beier et al, 2018;Evans and Clarke, 2018). N and water interact in significant ways that affect wheat growth.…”
Section: Introductionmentioning
confidence: 99%
“…The translocation happens over two pathways, first is the direct long‐distance transport of urea, and second is the transport of amino acids, which were assimilated by the GS/GOGAT cycle after the hydrolysis of urea to ammonium, as shown on the plant level for Arabidopsis and rice in Figure 1A,B. The mechanism of N translocation should be the same in Arabidopsis and rice, though experimental evidence for both plants is not complete; In Arabidopsis, a urea leach from the petiole was observed (Figure 1A; Bohner et al, 2015), and in rice the N translocation was shown by 15 N (Figure 1B, Beier et al, 2019). The pathway of urea degradation in the tissue itself in rice is again supported by the co‐localization of major pathway enzymes like urease, arginase, and GS/GOGAT isoforms in senescing tissues (Yabuki et al, 2017; Yamaya & Kusano, 2014).…”
Section: Dur3 Function In Senescing Leavesmentioning
confidence: 91%
“…A broader picture of the DUR3 involvement can be seen when its localization is taken into account. In Arabidopsis and Oryza sativa (rice), the localization of DUR3 in senescing leaves was primarily in the vascular system, and the involvement in nitrogen translocation was experimentally confirmed in both species (Beier et al, 2019; Bohner et al, 2015). The translocation happens over two pathways, first is the direct long‐distance transport of urea, and second is the transport of amino acids, which were assimilated by the GS/GOGAT cycle after the hydrolysis of urea to ammonium, as shown on the plant level for Arabidopsis and rice in Figure 1A,B.…”
Section: Dur3 Function In Senescing Leavesmentioning
confidence: 98%
See 1 more Smart Citation